2022
DOI: 10.1007/s13762-022-04274-w
|View full text |Cite
|
Sign up to set email alerts
|

A review of the recent development, challenges, and opportunities of electronic waste (e-waste)

Abstract: This study reviews recent developments, challenges, and the prospect of electronic waste (e-waste). Various aspects of e-waste, including collection, pre-treatment, and recycling, are discussed briefly. It is found that Europe is the leading collector of e-waste, followed by Asia, America, Oceania, and Africa. The monetary worth of e-waste raw materials is estimated to be $57.0 billion. However, only $10.0 billion worth of e-waste is recycled and recovered sustainably, offsetting 15.0 million tonnes (Mt) of CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(35 citation statements)
references
References 47 publications
0
34
0
1
Order By: Relevance
“…According to Mohideen et al [23] the respondents demonstrated a high degree of awareness as well as an adequate level of understanding of the significance of e-waste management. Shahabuddin et al [24] noted that country-specific standards and legislation, public awareness, effective implementation, and government incentives for creating cost-effective technologies are sought in order to effectively manage e-waste, which will play a significant role in the circular economy.…”
Section: E-waste Managementmentioning
confidence: 99%
“…According to Mohideen et al [23] the respondents demonstrated a high degree of awareness as well as an adequate level of understanding of the significance of e-waste management. Shahabuddin et al [24] noted that country-specific standards and legislation, public awareness, effective implementation, and government incentives for creating cost-effective technologies are sought in order to effectively manage e-waste, which will play a significant role in the circular economy.…”
Section: E-waste Managementmentioning
confidence: 99%
“…Therefore, one of the main goals of the article is to propose a method for calculating the scores of the PMS traits and measurements in the case study of the paper by adopting SCOR. To achieve these goals, the Supply Chain Operations Reference model is adjusted for the Performance Management System of the case under investigation using the Best-Worst Method and Nominal Group Technique (Shahabuddin et al, 2022). Despite SCOR's many benefits for assessing the performance of supply chains, certain extra modifications are needed to be made so that it can be tailored for particular uses, as in the case of the sustainable e-waste supply chain in this research.…”
Section: Figure2 Types Of E-waste Source: Author's Own Elaborationmentioning
confidence: 99%
“…The disposal of liquid crystal display (LCD) panels in landfills poses a risk not only to workers but also to the environment owing to the toxic contents of e-waste such as lead (Pb), mercury (Hg), and cadmium (Cd). As e-waste contains a wide range of materials, it is acting as a valuable source of different raw materials . However, only a small portion of e-waste is recycled globally due to the complexity of collection and difficult recycling methods used at present .…”
Section: Introductionmentioning
confidence: 99%
“…As e-waste contains a wide range of materials, it is acting as a valuable source of different raw materials. 3 However, only a small portion of e-waste is recycled globally due to the complexity of collection and difficult recycling methods used at present. 4 Hence, it is highly essential to identify proper methods and technologies with a greater focus on recycling and improved e-waste management.…”
Section: ■ Introductionmentioning
confidence: 99%